2020 International Conference on Intelligent Data Science Technologies and Applications (IDSTA) 2020
DOI: 10.1109/idsta50958.2020.9264030
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Existing and New Deep Learning Methods for Detecting Knee Injuries using the MRNet Dataset

Abstract: This work presents a comparative study of existing and new techniques to detect knee injuries by leveraging Stanford's MRNet Dataset. All approaches are based on deep learning and we explore the comparative performances of transfer learning and a deep residual network trained from scratch. We also exploit some characteristics of Magnetic Resonance Imaging (MRI) data by, for example, using a fixed number of slices or 2D images from each of the axial, coronal and sagittal planes as well as combining the three pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 10 publications
0
15
0
Order By: Relevance
“…The accuracy achieved by the radiologists (92%) was higher than the one achieved by the AI model (86.7%). Azcona et al [ 52 ] proposed and evaluated the performance of four architectures: (i) deep residual network with transfer learning; (ii) custom deep residual network using a fixed number of slices; (iii) multi-plane deep residual network; and (iv) multi-plane multi-objective deep residual network. They found that transfer learning combined with a carefully tuned data augmentation strategy were the crucial factors in achieving best performance.…”
Section: Resultsmentioning
confidence: 99%
“…The accuracy achieved by the radiologists (92%) was higher than the one achieved by the AI model (86.7%). Azcona et al [ 52 ] proposed and evaluated the performance of four architectures: (i) deep residual network with transfer learning; (ii) custom deep residual network using a fixed number of slices; (iii) multi-plane deep residual network; and (iv) multi-plane multi-objective deep residual network. They found that transfer learning combined with a carefully tuned data augmentation strategy were the crucial factors in achieving best performance.…”
Section: Resultsmentioning
confidence: 99%
“…Our study, by employing the efficiently-layered network (ELNet) rather than the ResNet50 model in the Model 3 section, can be re-evaluated. The study by Azcona et al [18] employed a logistic regression-based ensemble learning approach. The ROC-AUC values acquired from the study were 0.9557 for ACL, 0.9081 for meniscus, and 0.9381 for abnormality diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Each image is 256 × 256, and the number of slices ranges from 17 to 61. There are 1104 abnormal, 319 ACLs, and 508 menisci in the dataset [18]. The dataset contains 1130 trains, 120 valid, and 120 test datasets.…”
Section: Datasetmentioning
confidence: 99%
See 1 more Smart Citation
“…Tsai et al (2020) proposed a so-called “Efficiently-Layered Network” for detection of meniscal tears, reaching an AUC of 0.904 and 0.913 for two different datasets. Azcona et al (2020) demonstrated the use of a 2D CNN as a pseudo-3D variant for detection of torn menisci. Their method relies on transfer learning while using data augmentation and reaches an AUC of 0.934.…”
Section: Introductionmentioning
confidence: 99%